Application of The Cooperative Learning Model Student Teams Achievement Division Type in Developing Social Skills in Physical Education Learning - Reza Syaef Nuralie; Tite Juliantine; Burhan Hambali (Universitas Negeri Semarang, 2026)
Physical Education (PE) learning in junior high school tends to be teacher-centered and focused on technical mastery, thus insufficiently facilitating the development of students’ social skills. This study aims to examine the application of the Cooperative Learning model STAD type in developing social skills of Grade VII junior high school students in PE learning. The method used was quasi-experimental with a Non-Equivalent Control Group design, involving 34 students in the experimental group and 36 students in the control group selected through purposive sampling. Social skills were measured using the SSIS-RS (7 domains, 37 items), validated against 76 respondents and yielding a Cronbach's Alpha reliability coefficient of 0.913. The result of the Independent Samples T-Test on posttest data showed a significant difference between the two groups (p = 0.003), and the Mann-Whitney U test on N-Gain Scores confirmed the superiority of the experimental group (p = 0.001). It is concluded that the STAD-type cooperative learning model is significantly more effective in developing students’ social skills compared to conventional learning, through a structured positive interdependence mechanism.